Two unusual species of Polypedilum Kieffer (Diptera: Chironomidae) from Oriental China - Zhang, Ruilei L.; Wang, Xinhua; Sæther, Ole A. (Zootaxa, 2006)
Polypedilum (Cerobregma) paucisetum sp. n. and P. (Tripodura) nudiprostatum sp. n., with peculiar superior volsellae are described as male imagines from Oriental China. P. (C.) paucisetum has an Uresipedilum-like superior volsella. The superior volsella of P. (T.) nudiprostatum is slender and non-clavate with 11–13 apical setae. A phylogenetic analysis places P. (C.) paucisetum as the sister species of the remaining members of the subgenus. P. (T.) nudiprostatum apparently belongs to the pullum group of Tripodura.